2015
DOI: 10.1007/s00784-015-1448-x
|View full text |Cite
|
Sign up to set email alerts
|

Pain after single-visit root canal treatment with two single-file systems based on different kinematics—a prospective randomized multicenter clinical study

Abstract: Reciprocation movement offers a more predictable and safer approach of root canal preparation, in addition to producing less postoperative pain. The need for patients to take analgesics may reduce following this approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 37 publications
2
99
1
2
Order By: Relevance
“…These findings are not in concordance with our results. However, a recent report by Neelakantan and Sharma 4 (2015) concluded that Reciproc showed significantly less intensity and duration of postoperative pain compared with One Shape. Shokraneh, et al 12 (2016) evaluated postoperative pain after using hand files, ProTaper Universal, and Wave-One instruments and concluded that postoperative pain was significantly lower in Wave-One group.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…These findings are not in concordance with our results. However, a recent report by Neelakantan and Sharma 4 (2015) concluded that Reciproc showed significantly less intensity and duration of postoperative pain compared with One Shape. Shokraneh, et al 12 (2016) evaluated postoperative pain after using hand files, ProTaper Universal, and Wave-One instruments and concluded that postoperative pain was significantly lower in Wave-One group.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Neelakantan and Sharma 4 (2015) and Nekoofar, et al 5 (2015) evaluated postoperative pain after instrumentation of root canals with a single-file reciprocating or rotary file systems. However, one may argue that the different cross-sections, speed, kinematics, and systems may have had an impact on the postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations